The investigation of soil dielectric influence towards terrestrial background radiation - Mohd Jafery, Khawarizmi (2018)
A study on correlation between terrestrial radiation and dielectric property of various soil species in Johor state, Malaysia were investigated in this research. Total 11 soil species were randomly selected around Batu Pahat, Kluang and Johor Bahru. The soil species identified were Kranji, Linau-Sedu, Selangor-Kangkong, Peat, Telemong-Akob, Holyrood-Lunas, Batu Anam-Melaka-Tavy, Rengam-Jerangau, Kulai–Yong Peng and Steepland soils. All the samples were dried, grinded and sieve into fine powder for the elemental compositions and dielectric properties measurement. The correlation between terrestrial radiation and dielectric property of soils were measured statistically to measure the significance between each parameter study. Prior to that, terrestrial gamma radiation was found in Rengam Jerangau has the highest average reading of exposure dosage (97.33 ± 40.27 μR hr -1) while the Peat soil gives the lowest reading of (7.67 ± 1.15 μR hr -1). This was due to the differences in geological formation for Rengam Jerangau and Peat. For SEM/EDX, the average major atomic percentages found in each soil type are Si, Al, and C, while Fe and K are only minor. In addition, the 238U, 232Th and 40K concentrations were determined using HPGe and it was found that the majority of these three elements existed in Rengam Jerangau and Steepland based on the results of radionuclides and concentration activities. While for the dielectric property, all the samples soil was measured using Dielectric Assessment Kit (DAK) between frequencies 100 MHz to 3 GHz. Selangor Kangkong soil dominated the higher value of complex permittivity (2.6-4.5) and the lowest was found in Peat (1.5 -2.5). While for dielectric constant, Selangor Kangkong ‘B’ led the higher value of dielectric constant and the lowest still belonged to Peat soil. In conclusion, correlation was achieved by using Pearson's correlation and hypothesis testing, which states that there was no significant evidence based on r-value was below 0.5 and p-value exceed the significant level 0.05. It indicates that there was a no relationship between the natural background radiation and the dielectric properties of the soil.